Demography of a subarctic population of Clethrionomys gapperi : size and growth - Fuller, W. A. (Canadian Journal of Zoology, 1977)
Neither mean weight nor mean length of samples of Clethrionomys gapperi trapped in May was correlated with population size, spring weather, or mean age of the animals. Winter-caught samples showed no growth in length between September and April, but rapid growth from April to May. The ratio of May length to length the previous fall, used as an index of growth, was strongly correlated with mean maximum temperature for the period 16 April to 15 May (r = 0.89 for males, 0.97 for females). Weight declined from September to April, then increased rapidly from April to May. The ratio of May weight to weight the previous fall was correlated with spring temperature in 4 years out of 5. The exception was the peak spring of 1974, when increase in weight was greater than expected in view of the low temperature. This suggests that the animals in the peak spring were qualitatively different from those in other years, but that the difference was expressed as rapid growth rather than as large size per se. It is suggested that spring growth may be a more useful indicator of changes in the quality of individuals in fluctuating microtine populations than absolute size in spring.